Effects of Celangulin IV and V From Celastrus angulatus Maxim on Na+/K+-ATPase Activities of the Oriental Armyworm (Lepidoptera: Noctuidae). Issue 1 (20th June 2016) - Cheng, Dan; Feng, Mingxing; Ji, Yufei; Wu, Wenjun; Hu, Zhaonong
Abstract: Na + /K + -ATPase (sodium pump) is an important target for the development of botanical pesticide as it is responsible for transforming chemical energy in ATP to osmotic work and maintaining electrochemical Na + and K + gradients across the cell membrane of most animal cells. Celangulin IV (C-IV) and V (C-V), which are isolated from the root bark of Celastrus angulatus, are the major active ingredients of this insecticidal plant. The activities of C-IV and C-V on Na + /K + -ATPase were investigated by ultramicro measuring method to evaluate the effects of C-IV and C-V on Na + /K + -ATPase activities of the brain from the fifth Mythimna separata larvae and to discuss the insecticidal mechanism of C-IV and C-V. Results indicate that inhibitory activities of Na + /K + -ATPase by C-IV and C-V possess an obvious concentration-dependent in vitro. Compared with C-IV, the inhibition of C-V on Na + /K + -ATPase was not striking. In vivo, at a concentration of 25 mg/liter, the inhibition ratio of C-IV on Na + /K + -ATPase activity from the brain in narcosis and recovery period was more remarkable than that of C-V. Furthermore, the insects were fed with different mixture ratios of C-IV and C-V. The inhibition extent of Na + /K + -ATPase activity was corresponded with the dose of C-IV. However, C-V had no notable effects. This finding may mean that the mechanism of action of C-IV and C-V on Na + /K + -ATPase were different. Na + /K -ATPase may be an action target of C-IV and C-V.